THE INFLUENCES OF USING AUDIO VISUAL MEDIA TOWARDS GRAMMAR MASTERY OF ENGLISH EDUCATION STUDENTS AT JAMBI UNIVERSITY - Tubagus Zam Zam Al Arif (JAMBI-ENGLISH LANGUAGE TEACHING, 2018)
The objective of this study is to know whether audio visual media can be used to improve students’ grammar mastery of English education students. An experimental design was applied in this study. Participants of this study were 52 students of English Education at Jambi University. The students in the experimental and the control group were given the same materials. In the experimental group, students were taught by audio visual media. In the control group, students were not taught by audio visual media, they were taught in conventional way. A pre-test and post-test were administered to measure students’ grammar mastery before and after grammar classes in both of groups. Statistical analyses using an independent sample t-test were conducted to compare mean scores of the experimental group and the control group. The results revealed that audio visual media provides a differential effect in students’ grammar mastery gain for the lower and higher ability students in the experimental group. The result of this study showed; There is a significant effect between audio visual media and students’ grammar mastery. Test result obtained that p-value 0,002 (<0,05).